2023
DOI: 10.1017/s0047404523000040
|View full text |Cite
|
Sign up to set email alerts
|

Commemorative city-texts: Spatio-temporal patterns in street names in Leipzig, East Germany and Poznań, Poland

Abstract: This article contributes to research on commemorative naming strategies by presenting a comparative longitudinal study on changes in the urban toponymy of Leipzig (Germany) and Poznań (Poland) over a period of 102 years. Our analysis combines memory studies, linguistic landscape (LL) research and critical toponymy with GIS visualization techniques to explore (turnovers in) naming practices across time and space. The key difference between the two localities lies in the commemorative pantheon of referents—event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…The street name database for the research reported here was created by the German Research Foundation (DFG)-funded project Memory and Ideology in the Linguistic Landscape (MILL) that investigated commemorative (re-)naming in East Germany and Poland between 1916 and 2018. 5 The MILL street name database was further enhanced for Frankfurt (Oder).…”
Section: Main Textmentioning
confidence: 99%
“…The street name database for the research reported here was created by the German Research Foundation (DFG)-funded project Memory and Ideology in the Linguistic Landscape (MILL) that investigated commemorative (re-)naming in East Germany and Poland between 1916 and 2018. 5 The MILL street name database was further enhanced for Frankfurt (Oder).…”
Section: Main Textmentioning
confidence: 99%